Konsep Back to Ex Husband dalam Perspektif Islam - Aisya Aisya; Helniyani Helniyani; Putri Wulandari; Dwi Noviani (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
There was a divorce that broke the relationship between a husband and a wife. But there are other attempts to unite the couple through one word called reference. This study aims to describe and analyze the different references and reference procedures between the KHI and some of the Mazhab views. The research carried out using library research with the collection of data obtained from the study of the library (library research). The data received is divided into two primary data and secondary data. Furthermore, the data analysis techniques in this research are qualitative with deductive-inductive reasoning. The results of the study show that there is a reference difference in the view of the mazhab and KHI which is the maintenance of marriage. According to Mahab Shafi'i, the reference is to restore the status of marriage law in the midst of 'iddah after the occurrence of talak Raj'i. According to the hambali reference was to return to the state of the wife after the happening of the talak raj'i and is still in the iddah without repeating the interruption. Meanwhile, according to Imam Malik the referral is the return of the wives who have been interrogated other than Ba'in, with without doing interruptions and in the time of iddah. The husband who commits a ruse is a man who is lawful, reasonable, self-righteous, and not a murderer. According to Mazhab Syafi'i, the reference must be expressed in a clear or concise manner. However, according to the scholars, including Mazhab Hanafi, referrals are usually performed orally and are usually also performed directly by spouses. When the husband and wife of the village office are required to request a letter of reference for reference to KUA by showing an act of divorce issued by the Religious Court then to the office of religious affairs with the purpose of informing the KUA to reference, conducting examination, paying the fees of the registrar of references then issued the testimony has made a reference published by KUA and revoking the marriage book